Methodology for Studying the Ecological Quality of Furniture - Leon Oblak (University of Zagreb, Faculty of Forestry and Wood Technology, 2011)
Decisions for environment-friendly production and environmentally acceptable products are becoming a necessity and one of very important objectives of timber companies next to already existing economic criteria. Individual products and their manufacture have different infl uences on the pollution of the environment. Therefore it is necessary to determine the ecological quality of individual products, which means analyzing their ecological suitability during their life cycle. In our research we developed the methodology for establishing the ecological quality of furniture, based on three scientific methods: the method of life cycle analysis, ABC analysis, modified for our case, and the multi-criteria decision-making method. We analyzed the ecological quality of three kitchens of a well-known manufacturer. The results of the research are the basis for developing an optimal business strategy from the viewpoint of determining a production assortment. The used methodology is also suitable for studying other furniture products and for accepting optimal environmentally acceptable decisions in wood companies.